2021
DOI: 10.3390/ijerph18179170
|View full text |Cite
|
Sign up to set email alerts
|

Valid and Reliable Barbell Velocity Estimation Using an Inertial Measurement Unit

Abstract: The accurate assessment of the mean concentric barbell velocity (MCV) and its displacement are crucial aspects of resistance training. Therefore, the validity and reliability indicators of an easy-to-use inertial measurement unit (VmaxPro®) were examined. Nineteen trained males (23.1 ± 3.2 years, 1.78 ± 0.08 m, 75.8 ± 9.8 kg; Squat 1-Repetition maximum (1RM): 114.8 ± 24.5 kg) performed squats and hip thrusts (3–5 sets, 30 repetitions total, 75% 1RM) on two separate days. The MCV and displacement were simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
11
1
2
Order By: Relevance
“…Within the last decades, velocity-based resistance training (VBT) as an alternative strength training approach has gained increasing attention ( González-Badillo and Sánchez-Medina, 2010 ). During VBT the training intensity is controlled by monitoring the mean concentric velocity (MCV) of each repetition ( González-Badillo and Sánchez-Medina, 2010 ) using inertial sensors ( Held et al, 2021b ) or linear position transducers ( Held et al, 2021a ). In general, the level of fatigue increases gradually as a function of increasing effort during a training set ( Sánchez-Medina and González-Badillo, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Within the last decades, velocity-based resistance training (VBT) as an alternative strength training approach has gained increasing attention ( González-Badillo and Sánchez-Medina, 2010 ). During VBT the training intensity is controlled by monitoring the mean concentric velocity (MCV) of each repetition ( González-Badillo and Sánchez-Medina, 2010 ) using inertial sensors ( Held et al, 2021b ) or linear position transducers ( Held et al, 2021a ). In general, the level of fatigue increases gradually as a function of increasing effort during a training set ( Sánchez-Medina and González-Badillo, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that the validity of these devices was not evaluated in the current study due to the absence of a gold standard (i.e., the MOCAP system). In addition, the validity of GymAware, PUSH2 and Vmaxpro devices has been examined in previous studies using different approaches with con icting ndings reported, especially for PUSH2 and Vmaxpro devices 16,17 . Therefore, future research is required to comprehensively examine the validity of these devices.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, two wearable, wireless, IMU-based velocity monitoring devices PUSH2 (PUSH Inc., Toronto, ON, Canada) and Vmaxpro (alias EnodePro; Blaumann & Meyer-Sports Technology UG, Magdeburg, Germany) have grown in popularity among athletes and recreational trainees due to their versatility and relatively affordable price. Several studies [15][16][17] have examined the test-retest reliability of PUSH2 and Vmaxpro devices with free-weight exercises. However, it is important to highlight that the test-retest reliability assessment inevitably contains errors due to biological variation.…”
Section: Introductionmentioning
confidence: 99%
“…The Vmaxpro (Blaumann & Meyer-Sports Technology UG, Magdeburg, Germany) consists of a triaxial accelerometer, a gyroscope, and a magnetometer, weighing 16 g and measuring 4.5 × 2.7 × 1.2 cm. It has a sampling rate of 1000 Hz [ 31 ] and can be attached to metal surfaces by magnets or placed elsewhere using an elastic strap. This IMU is primarily designed for velocity-based resistance training [ 32 ], obtaining data from acceleration integration, so it can provide values for related variables such as peak velocity, average velocity, peak eccentric velocity, average eccentric velocity, percentage of force development, percentage of eccentric force development, average propulsive velocity, distance, and duration.…”
Section: Methodsmentioning
confidence: 99%